Rapid, Chemical-Free Generation of Optically Scattering Structures in Poly(ethylene terephthalate) Using a CO2 Laser for Lightweight and Flexible Photovoltaic Applications - Simon D. Hodgson; Alice R. Gillett (International Journal of Photoenergy)
Highly light scattering structures have been generated in a poly(ethylene terephthalate) (PET) film using a CO2 laser. The haze, and in some cases the transparency, of the PET films have been improved by varying the processing parameters of the laser (namely, scanning velocity, laser output power, and spacing between processed tracks). When compared with the unprocessed PET, the haze has improved from an average value of 3.26% to a peak of 55.42%, which equates to an absolute improvement of 52.16% or a 17-fold increase. In addition to the optical properties, the surfaces have been characterised using optical microscopy and mapped with an optical profilometer. Key surface parameters that equate to the amount and structure of surface roughness and features have been analysed. The CO2 laser generates microstructures at high speed, without affecting the bulk properties of the material, and is inherently a chemical-free process making it particularly applicable for use in industry, fitting well with the high-throughput, roll to roll processes associated with the production of flexible organic photovoltaic devices.